1999
DOI: 10.1021/la9902338
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Diffraction Study of the Effect of the Detergent Octyl Glucoside on the Structure of Lamellar and Nonlamellar Lipid/Water Phases of Use for Membrane Protein Reconstitution

Abstract: The phase behavior and structural parameters of dioleoylphosphatidylethanolamine (DOPE), monoolein (MO), and dipalmitoylphosphatidylcholine (DPPC) hydrated in excess aqueous phase containing micellar octyl glucoside (OG) were investigated by means of synchrotron X-ray diffraction in a wide range of temperatures. The lipid-to-detergent molar ratios were selected to be equal to those in a recent membraneprotein-reconstitution study. It was established that lipids displaying either nonlamellar (DOPE and MO) or la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
81
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(85 citation statements)
references
References 54 publications
2
81
2
Order By: Relevance
“…Tuning of the aqueous nanochannel sizes ( Figure 4) constitutes a means for control of their encapsulation capacity for biomolecules. In order to get insight into the mechanism of nanoconfinement of protein, peptides, or DNA in labyrinthine cubic network structures, [10][11][12][13][14][15][45][46][47][48][49][50][57][58][59] we discuss the monoolein cubic phase swelling as related to the changes in the lipid membrane curvature. The spontaneous monolayer curvature of the monoglyceride lipid assemblies is negative.…”
Section: Cubic Phase Swelling Via Stimuli-induced Modulation Of the Mmentioning
confidence: 99%
See 2 more Smart Citations
“…Tuning of the aqueous nanochannel sizes ( Figure 4) constitutes a means for control of their encapsulation capacity for biomolecules. In order to get insight into the mechanism of nanoconfinement of protein, peptides, or DNA in labyrinthine cubic network structures, [10][11][12][13][14][15][45][46][47][48][49][50][57][58][59] we discuss the monoolein cubic phase swelling as related to the changes in the lipid membrane curvature. The spontaneous monolayer curvature of the monoglyceride lipid assemblies is negative.…”
Section: Cubic Phase Swelling Via Stimuli-induced Modulation Of the Mmentioning
confidence: 99%
“…12,46,47,66 The monolayer curvature is reduced upon accommodation of such surfactant molecules at the apolar/polar interface and the aqueous nanochannels are enlarged ( Figure 4B). This corresponds to a cubic phase swelling and a structural change to a less curved structure with larger water channels 46 (D w ≈ 7 nm).…”
Section: Cubic Phase Swelling Via Stimuli-induced Modulation Of the Mmentioning
confidence: 99%
See 1 more Smart Citation
“…As OG is added to cubic MO (Qiu, 2000), the OG incorporates homogenously within the membrane moving the structure from a continuous packing of membranous blocks to a lamellar stacking of fluid membranous sheets. Similarly, when OG was added to a lamellar phase formed by DPPC, it also changed the phase from the viscoelastic gel to a fluid Lα lamellar phase generally only seen by DPPC at temperatures above its melting point (60). Other reports have showed that lamellar liposomes created from egg phosphatidyl choline and egg phosphatidic acid become solubilized by less than 10 mg/ml DM in solution (61; 62) and POPC vesicles were solubilized with alkyl ether with similar characteristics as decylmaltoside, where an increase in detergent composition moves the solution from a lamellar phase to a mixed micelle cubic phase (63; 64).…”
Section: Membranes and Alkyl Glycosides (Ags)mentioning
confidence: 99%
“…The addition of OG to DPPC and DOPE bilayers lead to a decrease in d-spacing, however detergents such as dodecyl sulfate are expected to increase the lamellar spacing (60; 68). OG decreases the inter-lamellar spacing of DOPE bilayers with increasing temperature, while increasing DPPC inter-lamellar spacing (60). DM had little effect, while dodecyl-β-d-glucopyranoside (DG) increased the spacing of DPPC lamellar structures at room temperature.…”
Section: Membranes and Alkyl Glycosides (Ags)mentioning
confidence: 99%